Spatiotemporal patterns of throwing muscle synergies in yips-affected baseball players - Toshiyuki Aoyama; Kazumichi Ae; Takahiro Taguchi; Yuna Kawamori; Daisuke Sasaki; Takashi Kawamura; Yutaka Kohno (Scientific Reports, 2024)
Abstract “Yips” are involuntary movements that interfere with the automatic execution of sports movements. However, how the coordination among the various muscles necessary for sports movements is impaired in athletes with yips remains to be fully understood. This study aimed to assess whether muscle synergy analysis through non-negative matrix factorization (NMF) could identify impaired spatiotemporal muscle coordination in baseball players with throwing yips. Twenty-two college baseball players, including 12 with and 10 without yips symptoms participated in the study. Electromyographic activity was recorded from 13 ipsilateral upper extremity muscles during full-effort throwing. Muscle synergies were extracted through NMF. Cluster analysis was conducted to identify any common spatiotemporal patterns of muscle synergies in players with yips. Whether individual players with yips showed deviations in spatiotemporal patterns of muscle synergies compared with control players was also investigated. Four muscle synergies were extracted for each player, but none were specific to the yips group. However, a more detailed analysis of individual players revealed that two of the three players who presented dystonic symptoms during the experiment exhibited specific patterns that differed from those in control players. By contrast, each player whose symptoms were not reproduced during the experiment presented spatiotemporal patterns of muscle synergies similar to those of the control group. The results of this study indicate no common spatiotemporal pattern of muscle synergies specific to the yips group. Furthermore, these results suggest that the spatiotemporal pattern of muscle synergies in baseball throwing motion is not impaired in situations where symptoms are not reproduced even if the players have yips symptoms. However, muscle synergy analysis can identify the characteristics of muscle coordination of players who exhibit dystonic movements. These findings can be useful in developing personalized therapeutic strategies based on individual characteristics of yips symptoms.